The impact of self-assessment, planning and goal setting, and reflection before and after revision on student self-efficacy and writing performance - Chung, Huy Q.; Chen, Vicky; Olson, Carol Booth (Reading & writing, 2021)
Writing on-demand, text-based analytical essays is a challenging skill to master. Novice writers, such as the sixth grade US students in this study, may lack background knowledge of how to compose an effective essay, the self-efficacy skills, and the goal setting skills that will help with completing this task in accomplished ways. This sequential mixed-method study explored the impact of guiding a predominantly Redesignated English Learner group of students in a large, urban, low-SES school district in a timed, on-demand essay into a multiple draft process paper through a self-assessment, planning and goal setting, and reflection process as they revised this process paper over a three week period. Both treatment and comparison students completed a pre-test on demand writing assessment, a pre and post self-efficacy in writing survey, and a post-test on demand writing assessment. Students in both conditions were participating in a year-long writing intervention called The Pathway to Academic Success, developed and implemented by the UC Irvine site of the National Writing Project (UCI Writing Project), during the 2017–2018 school year and received identical training from their teachers on how to revise a pre-test essay. However, only the treatment group engaged in self-assessment, planning and goal setting, and reflection during this revision process. Students in the treatment condition demonstrated improved self-efficacy in the writing sub-domain of revision ( p < .05) and had statistically significant greater gains on the post-test writing assessment (r = .57; p < .001). These results suggest that engaging students in a planned revision process that includes student reflection, planning, and goal setting before revision, and reflection and self-assessment after revision, positively impacts self-efficacy and writing outcomes.